Valuing the Deferred Tax Liability - Sansing, Richard (Journal of Accounting Research, 1998)
Using a model of corporate investment in which the deferred tax liability never reverses, I show that deferred taxes are a real economic burden whose value is the amount recognized multiplied by a fraction. The numerator of the fraction is the tax depreciation rate, and the denominator of the fraction is the sum of the tax depreciation rate and the cost of capital. Despite the requirement in Statement of Financial Accounting Standards No. 109: Accounting for Income Taxes (FASB [1992]), that a deferred tax liability or asset be recognized to reflect temporary differences between the book value and tax basis of assets, the valuation relevance of deferred taxes is an open question. Davidson [1958] shows that the deferred tax liability will grow indefinitely as long as investments generate new temporary differences at least as large as the temporary differences that reverse. Because deferred taxes are paid in the future but not discounted, their recognized values on financial statements are generally regarded to be overstated. Some have suggested their value is zero if the deferred tax liability never reverses; these arguments are cited in Stickney [1993,